2022
DOI: 10.3390/cancers14112731
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Current Status and Quality of Radiomics for Glioma Differential Diagnosis

Abstract: Radiomics is a promising tool that may increase the value of imaging in differential diagnosis (DDx) of glioma. However, implementation in clinical practice is still distant and concerns have been raised regarding the methodological quality of radiomic studies. Therefore, we aimed to systematically review the current status of radiomic studies concerning glioma DDx, also using the radiomics quality score (RQS) to assess the quality of the methodology used in each study. A systematic literature search was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 72 publications
2
9
0
Order By: Relevance
“…Additionally, none of the included studies met the high level of evidence criteria, as all were retrospective and lacked cost-effectiveness analyses. Our analysis also showed low scores in biologic correlations (9.09%) and open science/data (14.77%), which are similar to the limitations observed in radiomics models used for other purposes ( 44 46 ).…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, none of the included studies met the high level of evidence criteria, as all were retrospective and lacked cost-effectiveness analyses. Our analysis also showed low scores in biologic correlations (9.09%) and open science/data (14.77%), which are similar to the limitations observed in radiomics models used for other purposes ( 44 46 ).…”
Section: Discussionsupporting
confidence: 76%
“…Peripheral edema and peritumor in gliomas are two distinct concepts, the peritumor is typically an area within a specified radius around the tumor, whereas the peripheral edema around a glioma is irregular and frequently dispersed along the cerebral gyrus. Previous research has shown that the degree of peritumoral edema increases with the pathological grade and aggressiveness of glioma ( 14 ). It was demonstrated that individuals with severe edema (>10 mm) had mean or overall survival rates that were more than 50% lower than those with mild edema ( 8 , 9 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…In other fields of medicine, especially in oncology, radiomic analyses using statistical learning methods by analysing ultrasound [53,54], computed tomography [55][56][57], magnetic resonance [58,59], or positron emission tomography [60] images are very useful for differentiating between cancer and inflammation [61].…”
Section: Discussionmentioning
confidence: 99%